Language, culture and society - Mananay, Janet A.; Sumalinog, Gino G. (Cubao, Quezon City Lorimar Publishing Inc., 2021)
This is aligned to the current trends in education such as constructivist, integrative, interactive, collaborative, inquiry-based, brain-based, research-based, and reflective teaching-learning.
Chapter ONE: The Nature of Language and Language Study: Lesson 1: A Quick Look at Language, Macro Skills and Communicative Competence -- Lesson 2: First Language vs. Second Language -- Lesson 3: Macro and Micro Linguistic Studies -- Chapter TWO: Plurality of English: Lesson 1: World Englishes -- Lesson 2: Philippine English -- Lesson 3: Multilingualism -- Chapter THREE: Language and Humans: Lesson 1: Non-Human Communication -- Lesson 2: Features of Human Language by Hockett -- Lesson 3: Halliday's Language Functions -- Chapter FOUR: Language and Culture: Lesson 1: Accounts on the Origin of Language -- Lesson 2: Semiotics and Sign Language -- Lesson 3: Theories in Language and Culture -- Chapter FIVE: Language and History: Lesson 1: Historical Timeline of Noteworthy Linguists -- Lesson 2: Historical Development of the English Language -- Lesson 3: The English Language Family Tree -- Lesson 4: Old English, Middle and Modern English -- Chapter SIX: Applied Linguistics: Lesson 1: Ethnolinguistics -- Lesson 2: Code switching -- Lesson 3: Discourses of Language in Cultural and Social Relevance.
PAFTE Project WRITE.
OBE-Based.
Keywords: Language and culture; Sociolinguistics; Language and languages -- Study and teaching